A Regard on Parody from Russian Formalism: Laurence Sterne's "Tristram Shandy" - Djurdjevic, María (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The article tackles a revolutionary reading of the Laurence Sterne’s novel Tristram Shandy (1767) by Russian Formalism (V. Shklovsky, 1921), focused on the importance of its formal and parodic aspects. The novel has also been assessed as the first postmodern novel in history. But the parody is being used as a tool for metaliterary thinking from the times of the Ancient Greece. Thus, this text also tackles the principal milestone of the Russian Literature and Cultural Theory –its reconnecting with the pre- Modern philosophical tradition– illustrating how our hermeneutic work depends on the aesthetic norms of the cultural tradition we belong to.